A Novel Reconfigurable Array Antenna Using Metamaterial Structure - Nguyen, Ngoc Lan; Vu, Van Yem (Old Journal, 2017)
A novel compact 4x3 elements reconfigurable antenna array using PIN-diode for C and X band applications is presented in this paper. By using metamaterial structure on the ground plane, not only antenna's bandwidth is improved, but also the size of antenna is reduced. In addition, the gain of the proposed antenna array is improved by using Metamaterial Reflective Surface (MRS). The proposed antenna array is designed, simulated and fabriacated on FR4 substrate with thickness of 1.575 mm, εr=4.4 and tanδ=0.02. The proposed antenna is designed at center frequencies of 6.75 GHz and 9.3 GHz, respectively. The simulation results are obtained in CST Microwave Studio software and are compared to measurement ones.